2018
DOI: 10.1016/j.catcom.2018.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative conversion of lignin over cobalt-iron mixed oxides prepared via the alginate gelation

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…In most lignin degradation strategies, the macromolecule first ruptures into small fragments and then specific functional groups may selectively be removed or regenerated to produce higher quality products. However, specifically designed catalysts could directly convert lignin into these products while breaking specific chemical bonds and functionalities at once. , Due to the complex chemical structure of lignin, simple model compounds are typically used to facilitate the understanding of the lignin chemistry. In this work, we selected guaiacylglycerol-β-guaiacyl ether (GG) and veratrylglycerol β-guaiacyl ether (VG) model compounds to investigate lignin and UL oxidative depolymerization over heterogeneous catalysts (Scheme a). , They represent two of the most popular and widely used phenolic and non-phenolic lignin model compounds (with C γ –OH) featuring the β- O -4-aryl ether bond, dominating up to 50% of interunit linkages in softwood lignins. ,, These lignin-related model structures comprise carbon–carbon (e.g., C α –C β and C α –C ph ) and carbon–heteroatom (e.g., C β –OPh) bonds (Scheme a). The phenolic GG molecule is more reactive than the non-phenolic VG fragment because of the hydroxyl group on the benzene ring .…”
Section: Resultsmentioning
confidence: 99%
“…In most lignin degradation strategies, the macromolecule first ruptures into small fragments and then specific functional groups may selectively be removed or regenerated to produce higher quality products. However, specifically designed catalysts could directly convert lignin into these products while breaking specific chemical bonds and functionalities at once. , Due to the complex chemical structure of lignin, simple model compounds are typically used to facilitate the understanding of the lignin chemistry. In this work, we selected guaiacylglycerol-β-guaiacyl ether (GG) and veratrylglycerol β-guaiacyl ether (VG) model compounds to investigate lignin and UL oxidative depolymerization over heterogeneous catalysts (Scheme a). , They represent two of the most popular and widely used phenolic and non-phenolic lignin model compounds (with C γ –OH) featuring the β- O -4-aryl ether bond, dominating up to 50% of interunit linkages in softwood lignins. ,, These lignin-related model structures comprise carbon–carbon (e.g., C α –C β and C α –C ph ) and carbon–heteroatom (e.g., C β –OPh) bonds (Scheme a). The phenolic GG molecule is more reactive than the non-phenolic VG fragment because of the hydroxyl group on the benzene ring .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, main catalytic approaches for the up-grading of lignin involve a reacting atmosphere, either reductive (H2) to produce deoxygenated aromatics for energy use, or oxidative (O2, air) to produce oxygenated aromatics for fine chemistry [81]. As far as heterogeneous catalysis is concerned, oxygenated aromatics can be obtained particularly with perovskites [82], mixed-metal oxides such as FeCoO as demonstrated by Barakat and co. [83], all giving global yields into aromatic aldehydes (vanillin, syringal-dehyde…) in the 15-20 wt% range. Systems with supported metals have also been investigated with Co, Au, and Pd.…”
Section: Transformation Of Lignin Under Oxidative Atmospherementioning
confidence: 99%
“…36 Recently, considerable efforts were achieved in order to develop sustainable and eco-friendly procedures for oxides design. [37][38][39] Surya et al, prepared TiO 2 by using Jatropha curcas leaf extracts for the photocatalytic degradation of tannery wastewater. 40 Moreover, TiO 2 was synthesized from Cymbopogon proximus in order to use it for Rhodamine B photodegradation and the study suggested its possible use for drinking water purication.…”
Section: Introductionmentioning
confidence: 99%